Presurgical Nasoalveolar Molding of Bilateral Cleft Lip and Palate Infants: An Orthodontist's Point of View - Ayşe Tuba Altuğ (Galenos Yayinevi, 2017)
Nonsyndromic complete cleft lip and palate deformity is primarily functional, then esthetic, and finally but not least importantly, a dental challenge. Feeding and facial appearance are important during the first years of a newborn. Nutrition is universally provided by passive feeding plates. If the Cleft Team prefers to use active plates, alveolar molding combined with nasal approaches in infants is the best method to improve esthetics to date. Orthodontists are predominantly responsible for achieving both the goals. After those difficulties have been met in early days of the life, dentists are mainly responsible for the treatment thereafter. If the infants have a dentoalveolar unity without any fistulas and correctly aligned maxillary deciduous teeth, this is a real success. Therefore, this article is an overview of presurgical infant orthopedics and its contribution to subsequent dental practice.